For Brotherhood and Duty : The Civil War History of the West Point Class of 1862 - McEnany, Brian R. (American warriors (Lexington, Ky.), 2015)
During the tense months leading up to the American Civil War, the cadets at the United States Military Academy at West Point continued their education even as the nation threatened to dissolve around them. Students from both the North and South struggled to understand events such as John Brown's Raid, the secession of eleven states from the Union, and the attack on Fort Sumter. By graduation day, half the class of 1862 had resigned; only twenty-eight remained, and their class motto--"Joined in common cause"--had been severely tested. In For Brotherhood and Duty: The Civil War History of the West Point Class of 1862, Brian R. McEnany follows the cadets from their initiation, through coursework, and on to the battlefield, focusing on twelve Union and four Confederate soldiers. Drawing heavily on primary sources, McEnany presents a fascinating chronicle of the young classmates, who became allies and enemies during the largest conflict ever undertaken on American soil. Their vivid accounts provide new perspectives not only on legendary battles such as Antietam, Gettysburg, Fredericksburg, and the Overland and Atlanta campaigns, but also on lesser-known battles such as Port Hudson, Olustee, High Bridge, and Pleasant Hills. There are countless studies of West Point and its more famous graduates, but McEnany's groundbreaking book brings to life the struggles and contributions of its graduates as junior officers and in small units. Generously illustrated with more than one hundred photographs and maps, this enthralling collective biography illuminates the war's impact on a unique group of soldiers and the institution that shaped them.